PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA MELALUI PENERAPAN INOVASI PEMBELAJARAN TEKNO OLIM PADA SISWA KELAS VII D SMP NEGERI 2 GIRIMARTO TAHUN PELAJARAN 2022/2023 - Agus Sisyanto (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This classroom action research aims to increase motivation and learning outcomes through the application of innovative Waste Processing Technology (OLIM Techno) in science learning Ecosystem material for class VII D students of SMP Negeri 2 Girimarto, Academic Year 2022/2023. The object of the research is student motivation and learning outcomes in the science subject Ecosystem material. The types of data collected in the research are primary data and secondary data. Primary data sources are teachers and students, including summative test scores and observations during the learning process. Meanwhile, secondary data comes from colleagues who are observers. The results of this research show an increase in student learning outcomes, this can be seen from the percentage of learning completion in the pre-cycle learning which was 40%, in cycle 1 it became 70%, and became 90% in cycle 2. Student learning motivation in pre-cycle learning was relatively low, in cycle 1 to medium, and in cycle 2 high category. By implementing OLIM Techno learning innovations, teachers can change the paradigm from teacher-centered learning to student-centered learning.